2012
DOI: 10.1111/j.1365-2826.2011.02249.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Heme Oxygenase‐1 and Carbon Monoxide Excitatory Effects in Oxytocin and Vasopressin Neurones During Water Deprivation

Abstract: A growing body of evidence supports carbon monoxide (CO) as a gas neurotransmitter within the central nervous system. While CO has been shown to affect neurohypophyseal hormone release in response to osmotic stimuli, the precise sources, targets and mechanisms underlying CO actions within the magnocellular neurosecretory system remain largely unknown. In this study, we combined immunohistochemistry and patch-clamp electrophysiology to study the cellular distribution of the CO-synthase enzyme heme oxygenase typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 56 publications
2
35
1
2
Order By: Relevance
“…This is in agreement with previous studies showing HO-1 presence in astrocytes and their ability to contribute to CO bioavailability in other brain regions (Li et al, 2008; Mancuso, 2004; Schipper et al, 2009). Importantly, we found CO to tonically stimulate SON neuronal activity, having thus opposite effects to NO (Reis et al, 2012). Thus, astrocytes in the SON/PVN are important cellular sources of two opposingly acting gas gliotransmitters, NO and CO.…”
Section: - Astrocyte-to-neuron Signaling (Gliotransmitters)mentioning
confidence: 75%
See 1 more Smart Citation
“…This is in agreement with previous studies showing HO-1 presence in astrocytes and their ability to contribute to CO bioavailability in other brain regions (Li et al, 2008; Mancuso, 2004; Schipper et al, 2009). Importantly, we found CO to tonically stimulate SON neuronal activity, having thus opposite effects to NO (Reis et al, 2012). Thus, astrocytes in the SON/PVN are important cellular sources of two opposingly acting gas gliotransmitters, NO and CO.…”
Section: - Astrocyte-to-neuron Signaling (Gliotransmitters)mentioning
confidence: 75%
“…In fact, a growing body of evidence supports a modulatory role for CO on OT and VP release (Gomes et al, 2010; Mancuso et al, 1999). In a recent study, we reported HO1 to be expressed not only on SON/PVN magnocellular neurons, but also in astrocytes within these nuclei (Reis et al, 2012). This is in agreement with previous studies showing HO-1 presence in astrocytes and their ability to contribute to CO bioavailability in other brain regions (Li et al, 2008; Mancuso, 2004; Schipper et al, 2009).…”
Section: - Astrocyte-to-neuron Signaling (Gliotransmitters)mentioning
confidence: 99%
“…Accordingly, inhibition of HO was shown to decrease the hyperosmolality-induced release of OT and ANP by the medial basal hypothalamus in vitro 56. Similarly, inhibition of this enzyme also induced a strong hyperpolarization and a decrease in the firing rate of magnocellular neurosecretory cells in water-deprived animals 55. In addition to acting individually, CO has also been shown to interact with the nitrergic system to control hydromineral homeostasis.…”
Section: Main Neural Pathways Involved In the Regulation Of Ecf Volummentioning
confidence: 96%
“…The higher magnification shows the anatomical relationship between CB 1R‐positive terminals (in green) and oxytocinergic magnocellular neurones (in red) of the SON ( c ) or PVN ( d ). Free‐floating sections of 30 μm were obtained on a cryostat and submitted to the procedures for fluorescent staining, as described previously . The primary and secondary antibodies used were: anti‐cannabinoid receptor 1 (dilution 1 : 1000, rabbit, #ab23703; Abcam, Cambridge, MA, USA) and anti‐ OT (dilution 1 : 20 000, guinea pig, #T‐4084; Bachem, Torrance, CA, USA), f luorescein isothiocyanate ‐conjugated donkey‐anti‐rabbit (dilution 1 : 250, #711‐095‐152; Jackson ImmunoResearch, Newmarket, UK) and Cy5‐conjugated donkey anti‐guinea pig (dilution 1 : 250, #706‐175‐148; Jackson ImmunoResearch).…”
Section: The Localisation Of Ecb Receptors: a Clue For Targets?mentioning
confidence: 99%